The Effect of Leadership, Workload, and Company Culture on Work Performance with Employee Engagement as an Intervening Variable - Anistiana Amaliyatus; Toni Herlambang; Feti Fatimah; Amalina Maryam Z (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of leadership, workload, and company culture on work performance with employee engagement as an intervening variable. The study used a quantitative approach with a census method on 135 employees at the Tempurejo District Office, Jember Regency. Data were collected through questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results showed that leadership, workload, and company culture had a positive and significant effect on work performance, both directly and indirectly through employee engagement. Employee engagement was proven to act as a mediating variable that strengthens the relationship between organizational factors and work performance. These findings emphasize the importance of effective leadership, proportional workload management, and a positive work culture, healthy companies in improving public sector employee engagement and performance.